(untitled) (Revista Española de Fisiología, 1993)
• Calcium Channel Modulators in Heart and Smooth Muscle. Basic mechanisms and Pharmacological Aspects. S. Abraham y G. Amitai, eds. (Proceedings of the 33rd Oholo Conference Eilat, Israel, 1989). Weinheim, 1990. 406 págs., 155 figs, y 26 tablas. Precio: DM 164. • Carbonic Anhydrase. From Biochemistry and Genetics to Physiology and Clinical Medicine. F. BotrE, G. Gros y B. T. Storey, eds. VCH. Weinheim, 1991. 479 págs., numerosas tablas y figuras. Precio: DM 186. • Isolated Hepatocytes Preparation. Properties and Applications. M. N. Berry, A. M. Edwards y G. J. Barrit. (Laboratory Techniques in Biochemistry and Molecular Biology, 21: R. H. Burdon y P. H. van Knippenberg, eds.). Elsevier. Amsterdam y Elsevier Science Publishing Co. Inc. Nueva York, 1991.480 págs., 28 figs, y 8 tablas. Precio: US 183; en rústica: US 71.50. • Rhythms in Fishes. A. Ali, ed. (NATO ASI Series. Series A: Life Sciences, 236). Plenum Press. Nueva York, 1992,396 págs., 86 figs, y 12 tablas. Precio: US 95. • Bioluminiscence Analysis. S. Brolin y G. Wettermark. Weinheim, 1992. 161 págs., 80 figs, y 6 tablas. Precio: DM 136. • New Insights in Vertebrate Kidney Function. J. A. Brown, R. J. Balment y J. C. Rankin, eds. (Society for Experimental Biology, Seminar Series, 52). Cambridge University Press. Cambridge, 1993. 403 págs., 81 figs, y 21 tablas. Precio: £ 75.00. • The Biology of Neuropeptide Y and Related Peptides. Colmers y C. Wahlestedt. Humana Press, Totowa, N. J. 580 págs., 142 figs, y 12 tablas. Precio: £ 104. • From Obesity to Diabetes. J.-P. Felber, K. J. Acheson y L. Tappy. John Wiley & Sons. Chichester, 1993. 310 págs., 119 figs, y 4 tablas. Precio: US 47.50. • Decapod Crustacea. F. W. Harrison y A. G. Humes. (Microscopic Anatomy of Invertebrates: F. W. Harrison, ed., Vol. 10). Wiley-Liss, Inc. Nueva York, 1992. 473 págs., 339 figs, y 10 tablas. Precio: US 79.95. • Fine Structure Immunocytochemistry. G. Griffiths. Springer-Verlag. Heidelberg, 1993. 480 págs., 90 figs, y 28 tablas. Precio: DM 148. • Perspectives on Animal Behavior. J. Goodenough, B. Macguire y R. Wallace. John Wiley & Sons, Inc. Nueva York, 1993. 80 págs., 468 figs., varias de ellas en color, y 29 tablas. Precio: US 21.50. • Regulation of the Eukaryotic Cell Cycle. J. Marsh, ed. (Ciba Foundation Symposium, 170). John Wiley & Sons. Chichester 1992. 298 págs., 44 figs, y 7 tablas. Precio: US 42.50. • Macrophages and Related Cells. M. A. Horton, ed. (Blood Cell Biochemistry, 5: J. R. Harries, ed.). Plenum Press. Nueva York, 1993. 453 págs. Precio: US 89.50. • Alzheimer’s Disease: Advances in Clinical and Basic Research. N. B. Corain, K. Iobal, M. Nicolini, B. Winblad, H. Wisniewski y P. Zatta. John Wiley & Sons, Inc. Chichester, 649 págs., 164 figs, y 60 tablas. Precio: US110. • Pratique de 1‘utilisation dessondes nucleiques et de Phybridation moleculaire. G. Lucotte. Lavoisier. Paris, 1992. 112 págs., 37 figs, y 5 tablas. Precio: 195 F. • Intramembrane Charge Movementsin Striated Muscle. Ch. L.-H. Huang. (Monographs of the Physiological Society, 44). Oxford University Press. Oxford, 1993. 302 págs., 74 figs, y 7 tablas. Precio: £ 45. • Nutrition and Immunology. D. M. Klurfeld, ed. (Human Nutrition: a Comprehensive Treatise, 8: R. B. Alfin-Slater y D. Kritchevsky). Plenum Press. Nueva York, 1993. 377 págs., 40 figs, y 43 tablas. Precio: US 79.50. • Intracellular Regulation of Ion Channels. Morad y Z. Agus. (NATO ASI Series. H: Cell Biology, 60). Springer-Verlag. Heidelberg, 1992. 251 págs. y 54 figs. Precio: DM 205. • Oxford Reviews of Reproductive Biology, 15, 1993. S. R. Milligan, ed. Oxford University Press. Oxford, 1993.376 págs., 52 figs, y 6 tablas. Precio: £ 50. • The Cytoskeleton of Flagellate and Ciliate Protists. M. Melkonian, R. A. Andersen y E. Schnepf, eds. Springer-Verlag. Viena, 1991. 172 págs. y 154 figs. Precio: DM: 198. • Marine Mammal Sensory Systems. J. Thomas, R. A. Kastelein y A. Y. Supin, eds. Plenum Press. Nueva York, 1992. 787 págs., 303 figs. y 54 tablas. Precio: US 149. • Calcium in Muscle Contraction (2/ edic.). J. C. Ruegg. Springer-Verlag, 1992. 354 págs., 110 figs, y 11 tablas. Precio: DM 133. • Pestizide im Boden. Microbieller Abbau und Nebenwirkunggen aufMikroorganismen. H. Domsch. VCH Weinheim, 1992. 585 págs., 34 figs, y 16 tablas. Precio: DM 225. • Voet y J. G. Voet. VCH. Weinheim, 1992. 1260 págs., numerosas tablas y figuras, gran parte en color. Precio: DM 138. • Molecular Genetics of Nervous System Tumors. Levine y H. H. Schmidek. Wiley-Liss. Nueva York, 1993.426 págs., 129 figs., varias en color, y 60 tablas. Precio: US 79.95. • Lexikon Gkotoxikologie. B. Streit. V. C. H. Weinheim, 1992. 750 págs. Precio: DM 124. • Growth Factors, Peptides, and Receptors. T. W. MOODY, cd. (GWUMC Department of Biochemistry Annual Spring Symposia: A. L. Goldstein, A. Kumar y J. M. Bailey, eds.) Plenum Press, Nueva York. 1993. 477 págs. Precio: U.S. 115.00. • Molecular Biology of Membranes. Structure and Function. H. R. Petty. Plenum Publ. Nueva York, 1993. 424 págs., 162 figs. y 25 tablas. Precio: U.S. 59.50. • Development of the Central Nervous System in Vertebrates. C. Sharma y A. M. Goffinet. (NATO ASI Series, A: Life Sciences, 234). Plenum Press. Nueva York, 1992. 288 págs., 101 figs. Precio: US 85. • Vitamin E Abstracts. Abstracts preparados por M. K. Horwitz. La Grange, Ill. 1992. 191 págs. Precio: gratis, a petición. • Frontiers and New Horizons in Amino Acid Research. K. Takai. Elsevier Science Publishers. Amsterdam: 1992. 726 págs. 265 figs, y 84 tablas. Precio: U.S. 231.50. • Pharmacology of the Respiratory Tract. Experimental and Clinical Research. K. F. Chung y P.J. Barnes, eds. (Lung Biology in Health and Disease, 67: C. Lenfant, ed.). M. Dekker. Nueva York. 1993. 840 págs., 115 figs, y 44 tablas. Precio: U.S. 195.00. • Practical HPLC Methodology and Applications. B. A. Bidlingmeyer. John Wiley & Nueva York, 1992. 452 págs., 224 figs. y 49 tablas. Precio: U.S. 45.50. • Pharmacologic Analysis of Drug-Receptor Interaction (2a. edic.). Raven Press. Nueva York, 1993. 495 págs., 292 ilustraciones. Precio: U.S. 113.50. • Brain Activation. P. E. Roland. Wiley-Liss. Nueva York, 1993. 598 págs., 258 figs., 18 de ellas en color, y 52 tablas. Precio: U.S. 84.95. • Human Protein Data. A. Haeberli, ed. VCH. Weinheim, 1992. Precio: DM 275.00.